The Impact of Microfinance on SME Growth Focusing on Savings and Investment Patterns: A Case Study of Mukono District - Hassan Mohamud (Uganda Christian University, 2024)
This paper aims to analyze the influence of microfinance on the development of small and medium enterprises (SMEs) in the Mukono district through an investigation of their saving and investment patterns. This paper examines the impact of financial services and training offered by microfinance institutions (MFIs) on these enterprises. This study assesses the impact of advising services on promoting the development of small and medium-sized enterprises (SMEs) in Mukono. Employing a mixed-method study methodology, data was collected from 52 small and medium-sized enterprise (SME) owners via interviews and questionnaires. The participants were selected using a purposive and simple random selection technique. The sample size was adjusted according to Krejcie and Morgan's (1970) table, which offers recommendations depending on the desired confidence level and margin of error for the study population. The findings suggest that microfinance plays a crucial role in assisting small and medium-sized enterprises (SMEs) in saving and obtaining easily available services. A significant proportion of participants confirmed that microfinance offers adaptable repayment alternatives, crucial business guidance, and training that improves their operational capacities and competitiveness. Training programmer that specifically targeted technical skills were highly recognized for their capacity to enhance the manufacturing processes of small and medium-sized enterprises (SMEs). In addition, participants expressed the view that receiving microfinance consultation on company strategy and resilience had a crucial role in enabling them to accomplish their business objectives within specified time limits. MFIs provide extensive assistance to SMEs, enabling them to effectively navigate financial environments and capitalize on strategic growth prospects. These findings emphasize the need for government assistance in expanding educational and financial resources to promote a strong entrepreneurial environment.